Complete mitochondrial genome of the black giant squirrel Ratufa bicolor (Rodentia: Sciuridae). (3rd September 2015) - Kong, Lingming; Wang, Wenquan; Cong, Haiyan; Liu, Zexin; Li, Yuchun
Abstract: The complete mitochondrial genome of black giant squirrel ( Ratufa bicolor ) from Hainan Island was sequenced and characterized in detail. The 16, 563 bp genome was composed of 13 protein-coding genes, 22 tRNAs, 2 rRNAs and 2 non-coding regions. The mitochondrial genome of R. bicolor presented in this report will be useful for species identification, conversation and clarifying the controversial taxonomic status of genus Ratufa .